MEMBANGUN PENDIDIKAN BERBASIS ISLAM NUSANTARA (PENDIDIKAN BERBASIS KARAKTER ATAU AKHLAKUL KARIMAH ?) - Hefniy, Hefniy (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2017)
Education is a planned effort in the process of guidance and learning for individuals to grow and grow into an independent human being, responsible, creative, knowledgeable, healthy, and noble good seen from the physical and spiritual aspects. Humans of noble character, who possess high morality are strongly demanded to be formed or built. Given the present and future conditions, the preparation of the next generation of characteristic nations is a vital necessity. This is done to prepare for global challenges and national competitiveness. Departing from the phenomenon, it is necessary strengthening the character of the students so that they can form a strong and tough person, which is done through education. Education is the most effective means to build and nurture the character of learners. character education aims to improve the quality of education implementation and results in schools that lead to the achievement of character formation and noble character of learners intact, integrated, and balanced in accordance with the principles derived from the cultural values of the nation and religion